SPECIFICITIES OF NON-INTELLIGENCE WORK OF MODERN SECURITY SERVICES (Heritage, 2025)
The security services, from their inception to the present day have played a very important, if not decisive, role in all major events that have taken place in states since their inception. Тhis role has varied exclusively from the intentions of the bearers of political systems and the nature of their activities. What unites all security services in the world are the objects of their security-related interest, which, depending on the time in which they take place, represent responses to current risks and threats directed against the state and society in every sense. The aim of this paper is to present the most common techniques of non-intelligence work of security services through a scientific description, as an instrument by which organized states from a position of power create their foreign policy and international position. The paper presents a comprehensive overview of the general theoretical definition of non-intelligence work with its classification and normative definition in individual international documents. A special part of the research concerns the identification of various forms of non-intelligence work of security services in practice, in relation to the organizational character and structure of the security service itself, where current events on a global level have shown that non-intelligence work of security services, due to the progress of new information technologies, has become an extremely important technique of intelligence and security systems of modern states and an indispensable security instrument of the state today. The result of this research are recommendations that it is necessary to intensively strengthen the counterintelligence potential of national intelligence and security systems, as a reaction to all identified and future techniques of non-intelligence work of security services. The paper uses the method of theoretical analysis and the deductive method to understand and explain subversive and non-subversive activities of non-intelligence work of security services.
Keywords: non-intelligence work, security service, specifics, subversive activities, covert actions (operations)